HUBUNGAN FACEBOOK ADDICTION DISORDER (FAD) DENGAN PERILAKU ASERTIF REMAJA DI SMA KRISTEN 1 TOMOHON (JURNAL KEPERAWATAN, 2014)
Abstract: Facebook addiction means spending excessive amounts of time on Facebook. Psychologically, the negative effects of facebook addiction can be divided into : Personal anti-social and Dualism personality. The purpose of this study was to determine the correlation between Facebook Addiction Disorder (FAD) with assertive behaviour of adolescent in Christian High School 1 Tomohon. The design of this study was conducted with cross sectional method, populations are all of the student in eleventh grade who have an active facebook account, selecting samples with purposive sampling. Analysis data using SPSS version 20 with chi-square test to determine the correlation between facebook addiction disorder with assertive behaviour of adolescent. Result of the study the prevalence of facebook addiction disorder in Christian Senior School 1 Tomohon in low categories and assertive behavior in good categories. The conclusion is there is a correlation between facebook addiction disorder with assertive behaviour of adolescent that obtained value (p=0,000